2008
DOI: 10.1021/ic801213z
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl-Functionalized Task-Specific Ionic Liquids for Solubilizing Metal Oxides

Abstract: Imidazolium, pyridinium, pyrrolidinium, piperidinium, morpholinium, and quaternary ammonium bis(trifluoromethylsulfonyl)imide salts were functionalized with a carboxyl group. These ionic liquids are useful for the selective dissolution of metal oxides and hydroxides. Although these hydrophobic ionic liquids are immiscible with water at room temperature, several of them form a single phase with water at elevated temperatures. Phase separation occurs upon cooling. This thermomorphic behavior has been investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
189
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(204 citation statements)
references
References 69 publications
8
189
1
2
Order By: Relevance
“…15 Thus, some task-specific solvents have been investigated to dissolve metal oxides. Binnemans et al 16,17 15 ZnO showed a high solubility in urea/choline chloride eutectics (8466 ppm), which was higher than that reported for the NaCl-KCl system at 973 K (only 27.6 ppm). In ZnO-urea/ choline chloride system, the species [ZnClO.urea] ¹ was discovered as dominated anions and no other zinc-containing clusters have been observed in this system.…”
Section: Introductionmentioning
confidence: 74%
“…15 Thus, some task-specific solvents have been investigated to dissolve metal oxides. Binnemans et al 16,17 15 ZnO showed a high solubility in urea/choline chloride eutectics (8466 ppm), which was higher than that reported for the NaCl-KCl system at 973 K (only 27.6 ppm). In ZnO-urea/ choline chloride system, the species [ZnClO.urea] ¹ was discovered as dominated anions and no other zinc-containing clusters have been observed in this system.…”
Section: Introductionmentioning
confidence: 74%
“…Only limited papers about the higher concentration of the lanthanide ions in ionic liquid have been reported. 12,15,[17][18][19] Incorporating lanthanide ions as an anion into ionic liquids is an effective way to increase the concentration of lanthanides. 13,14,16 An alternative approach to increase the solubility of metal salts is to use task-specific ionic liquids (TSIL) bearing a complexing moiety.…”
Section: -15mentioning
confidence: 99%
“…[15][16][17][18][19] This usally occurs at high acid conditions (low pH) and high chloride concentrations. 20 [25][26][27] of the IL. Regeneration of these functionalized IL is mainly done by reducing the metal interaction of the functionality due to protonation or oxidation, which can also be achieved with weaker acids and/or bases.…”
Section: Introductionmentioning
confidence: 99%